Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/foods11091208
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Acacia (Acacia seyal) and Cactus (Opuntia ficus-indica) Gums on the Dough Performance and Quality Attributes of Breads and Cakes

Abstract: Two hydrocolloids, acacia gum and cactus gum, were tested in the current study to see if they could improve the quality of the dough or have an effect on the shelf life of pan bread and sponge cake. Both gums considerably (p < 0.05) enhanced the dough development time, softness, and mixing tolerance index while decreasing the water absorption. Although the dough was more stable with the addition of acacia gum than with cactus gum, the control sample had the highest peak, final, breakdown, and setback viscos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Panelists from the Department of Food Science and Nutrition at King Saud University were chosen from among staff and graduate students. The attributes of the bread samples such as aroma, taste, texture, and general acceptability were graded on a 9-point hedonic scale by the evaluators, with 9.0 denoting extremely good and 1.0 denoting extremely poor [44]. A skilled group of judges conducted a sensory analysis of the bread samples.…”
Section: Sensory Evaluation Of Breadsmentioning
confidence: 99%
“…Panelists from the Department of Food Science and Nutrition at King Saud University were chosen from among staff and graduate students. The attributes of the bread samples such as aroma, taste, texture, and general acceptability were graded on a 9-point hedonic scale by the evaluators, with 9.0 denoting extremely good and 1.0 denoting extremely poor [44]. A skilled group of judges conducted a sensory analysis of the bread samples.…”
Section: Sensory Evaluation Of Breadsmentioning
confidence: 99%
“…Porosity primarily results from the presence of carbonic acid, carbon dioxide and other ingredients. The development of the gluten network gives rise to a spongy hollowness, crucial for maintaining the structural integrity and preventing collapse (Hussain et al ., 2022). As the addition of cheese powder increased, the number of porosities decreased on the bread, and it had a tighter structure.…”
Section: Resultsmentioning
confidence: 99%
“…Following this, the cylinder was tapped, and the sample's volume was measured to calculate the tapped density of the powder. The tapped density (g t ) was determined by dividing the same mass of the powder by the tapped volume of the powder in the cylinder (Jinapong et al, 2008).…”
Section: Bulk and Tapped Densitymentioning
confidence: 99%
“…First, it can be used as a natural thickening agent in various food products such as sauces, soups, and bakery items, improving their texture and mouthfeel. Hussain et al [ 70 ] reported decreased bread hardness after 24 h when using cactus gum from Opuntia ficus-indica compared to acacia seyal gum, which is another dietary fiber. Second, cactus fiber can enhance the nutritional profile of food products, meeting the demand of health-conscious consumers seeking out high-fiber diets.…”
Section: Functional Ingredients Derived From Cactus Species For the F...mentioning
confidence: 99%